Freehand Minimally Invasive Pedicle Screw Fixation and Minimally Invasive Decompression for a Thoracic or Lumbar Vertebral Metastatic Tumor From Hepatocellular Carcinoma - Fan, Wenshuai; Zhou, Tianyao; Li, Jinghuan; Sun, Yunfan; Gu, Yutong (Frontiers in Surgery, 2021)
Objective: To compare freehand minimally invasive pedicle screw fixation (freehand MIPS) combined with percutaneous vertebroplasty (PVP), minimally invasive decompression and partial tumor resection with open surgery for treatment of thoracic or lumbar vertebral metastasis of hepatocellular carcinoma (HCC) with symptoms of neurologic compression, and evaluate its feasibility, efficacy and safety. Methods: A total of 47 patients with 1-level HCC metastatic thoracolumbar tumor and neurologic symptoms in our hospital between February 2016 and April 2017 were included. Among them, 21 patients underwent freehand MIPS combined with PVP, minimally invasive decompression and partial tumor resection (group 1), while 26 patients were treated with open surgery (group 2). Duration of operation, blood loss, times of fluoroscopy, incision length and stay at the hospital were compared between the groups. Pre- and postoperative visual analog scale pain scores (VAS), American Spinal Injury Association (ASIA) grade, ambulatory status, and urinary continence were also recorded. The Cobb angles, central, and anterior vertebral body height were measured on the lateral radiographs before surgery and during the follow-up. Results: Patients in group 1 showed significantly less blood loss (195.5±169.1ml vs 873.1±317.9ml, P=0.000), shorter incision length (3.4±0.3cm vs 13.6±1.8cm, P=0.000), shorter median stay at the hospital (4-8/6 days vs 8-17/12 days, P=0.000), more median times of fluoroscopy (5-11/6 times vs 4-7/5 times, P=0.000) and longer duration of operation (204.8±12.1min vs 171.0±12.0min, P=0.000) than group 2 did. Though VAS significantly decreased after surgery in both groups, the VAS of group 1 was significantly lower than that of group 2 immediately after surgery and during the follow-up (P<0.05). No differences in the neurological improvement and spinal stability were observed between the two groups. Conclusion: Freehand MIPS combined with PVP, minimally invasive decompression and partial tumor resection is safe, effective and minimally invasive method for treating thoracolumbar metastatic tumors of liver cancer, with less blood loss, better pain relief, shorter length of midline incision and stay at the hospital.